2022
DOI: 10.1038/s41467-022-31747-w
|View full text |Cite
|
Sign up to set email alerts
|

A calibratable sensory neuron based on epitaxial VO2 for spike-based neuromorphic multisensory system

Abstract: Neuromorphic perception systems inspired by biology have tremendous potential in efficiently processing multi-sensory signals from the physical world, but a highly efficient hardware element capable of sensing and encoding multiple physical signals is still lacking. Here, we report a spike-based neuromorphic perception system consisting of calibratable artificial sensory neurons based on epitaxial VO2, where the high crystalline quality of VO2 leads to significantly improved cycle-to-cycle uniformity. A calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 67 publications
0
109
0
Order By: Relevance
“…Therefore, the statistical analysis of our MSC-VFET indicates a high SNR of 114.15 dB when the applied gate pulses are −60 V and the valid read-out I DS is set as 0.02 mA cm −2 , which is far beyond most reported experimental cases. [64,65]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the statistical analysis of our MSC-VFET indicates a high SNR of 114.15 dB when the applied gate pulses are −60 V and the valid read-out I DS is set as 0.02 mA cm −2 , which is far beyond most reported experimental cases. [64,65]…”
Section: Resultsmentioning
confidence: 99%
“…Recently, emerging devices, such as memristors, have been used to emulate the functionalities of synapses and neurons. Yuan et al 91 reported a neuromorphic perception system that can monitor the curvatures of fingers by using the perception component VO 2 (Fig. 6b ).…”
Section: Applications Of Neuron Devicesmentioning
confidence: 99%
“… a Scheme of the biological perception system. b Response of artificial spiking curvature sensory neurons to the gesture ‘Two’ and corresponding statistics of spiking frequency 91 . Copyright 2022 Springer Nature.…”
Section: Applications Of Neuron Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an optic-neural synaptic device based on an optical sensing transistor and a synaptic transistor connected in series was proposed, which is able to classify color-mixed patterns with a full-connected optic-neural network 20 . More recently, the artificial spiking receptors has aroused great interesting based on a consensus that information implied in rate is extremely energy-efficient and very robust to noise [23][24][25][26][27][28][29][30] . A spiking photoreceptor based on an optical sensor and oscillation neuron in series exhibited efficient edge image segmentation out of a complex background, representing a pioneer and feasible approach toward spiking cone photoreceptor 10 .…”
Section: Introductionmentioning
confidence: 99%